2008
DOI: 10.1097/jto.0b013e31818026f6
|View full text |Cite
|
Sign up to set email alerts
|

Wood-Smoke Exposure as a Response and Survival Predictor in Erlotinib-treated Non-small Cell Lung Cancer Patients: An Open Label Phase II Study

Abstract: WSE is associated with better response to Erlotinib and improved progression-free survival in patients with NSCLC. Additional studies in epidermal growth factor receptor signaling pathway in WSE-associated NSCLC are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
(39 reference statements)
1
16
0
Order By: Relevance
“…Nonetheless, after adjusting for sex, ECOG status, and histological type, it was found that a background of WSE was the most important independent factor associated with longer survival and response, having 83.3% overall response and 17.6 months PFS. 15 Similar studies have reported that WSE is a predictor of gefitinib responsiveness. 20 It has already become well established that EGFR gene mutations confer special sensitivity on TKIs such as gefitinib, erlotinib, and afatinib, 12 leading to 60% to 80% objective response and 8 to 16.5 month PFS rates.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Nonetheless, after adjusting for sex, ECOG status, and histological type, it was found that a background of WSE was the most important independent factor associated with longer survival and response, having 83.3% overall response and 17.6 months PFS. 15 Similar studies have reported that WSE is a predictor of gefitinib responsiveness. 20 It has already become well established that EGFR gene mutations confer special sensitivity on TKIs such as gefitinib, erlotinib, and afatinib, 12 leading to 60% to 80% objective response and 8 to 16.5 month PFS rates.…”
Section: Discussionmentioning
confidence: 59%
“…13,14 Our group conducted a clinical trial using EGFR-TKIs as treatment for patients having progression to first-or second-line chemotherapy; 28% of the patients in our group had a history of WSE and were associated with better EGFR-TKI response rate (RR) (83.3%) and improved progression-free survival (PFS) of 17.6 months. 15 The clinical and pathological characteristics, genotype (EGFR and KRAS), and response to chemotherapy, EGFR-TKIs, and clinical outcomes were investigated regarding lung cancer patients at our institution.…”
mentioning
confidence: 99%
“…Environmental exposures specifically associated with lung cancer in H/L include exposure to wood-smoke, asbestos, asphalt and tar [68, 69]. For example, heating and cooking with open fires in poorly ventilated places, can cause high indoor smoke levels.…”
Section: Hispanics/latinos and Lung Cancermentioning
confidence: 99%
“…Besides the known effects of inorganic gases (e.g., NOx and CO), cilia-toxic respiratory irritants (e.g., phenols, cresols, acrolein, and acetaldehyde) and carcinogenic or mutagenic organic compounds (e.g., benzene, formaldehyde, 1,3-butadiene, PAH, and quinones) in biomass smoke are also known to pose health hazards [26]. As mentioned, numerous epidemiology and occupational studies have confirmed that biomass smoke exposure is associated with adverse respiratory and cardiovascular outcomes [26][27][28] and increased risk of lung cancer [29,30]. However, toxicology studies are still needed to fully explain the key component(s) of the biomass smoke responsible for adverse health outcomes and how these constituents differ depending on fuel and combustion conditions [26,31].…”
Section: Effects Of Organic Compounds In Wildfire Pm On Lung Inflammamentioning
confidence: 92%